Phylogeography, genetic structure and wing pattern variation of Erebia pronoe (Esper, 1780) (Lepidoptera: Nymphalidae) in Europe - Paučulová, Lenka; Dzurinka, Maroš; Šemeláková, Martina; Csanády, Alexander; Panigaj, Ľubomír (Zootaxa, 2018)
The distribution of genetic diversity within Erebia pronoe (Esper, 1780) populations in relation to biogeographic ranges is essential for understanding the processes of evolution, speciation and phylogeography in this species. A certain degree of genetic variability was expected because of the species’ linkage solely to calcareous soils. These ideas were focused on the water ringlet E. pronoe, a European endemic montane butterfly distributed over a narrow area of mountains, with its occurrence dependent on nutrient plants. Therefore, the origin, occurrence, phylogeography and variability are described in defined mountain localities in Europe in the light of glaciation events that occurred during the Quaternary (Pleistocene) period. The species’ phylogeography is based on a combination of two mitochondrial genes (COI, CR) and morphology (wing morphometry). The study comprised samples from the Western Carpathians, Pyrenees, Alps, South-Eastern Carpathians (Romania) and Southern Limestone Alps (Slovenia). Moreover, the species’ remarkable phylogeographic structure was observed, including four morphologic lineages and divergent genetic lineages. These lineages cover the Carpathian Mountains as well as the Western European mountains (Spanish populations) with no apparent gene flow between most regions, even across distances of only hundreds of kilometres.